PELATIHAN SENAM HIPERTENSI SEBAGAI UPAYA PENGENDALIAN TEKANAN DARAH LANSIA - Istiqomah Istiqomah; Elisabeth Iswantiningsih; Sumarti Endah Purnamaningsih Maria Margaretha; Ismi Nur Khasanah (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2025)
Hypertension is one of the most common non-communicable diseases among the elderly and can reduce quality of life if not properly managed. Non-pharmacological interventions such as health education and hypertension exercise are effective strategies to control blood pressure. This community service activity aimed to improve elderly knowledge and assist blood pressure control through health education and hypertension exercise. The activity was conducted in Mangir Lor Village, Sendangsari, Pajangan, Bantul Regency, involving five elderly participants aged 64–75 years. The methods included initial observation, health education on hypertension, hypertension exercise practice, and monitoring exercise implementation three times per week. The results showed an improvement in the elderly’s understanding of hypertension and the benefits of physical activity, as well as a tendency toward decreased blood pressure after regularly participating in hypertension exercise. Participants also demonstrated good enthusiasm and were able to recall the educational material provided. This activity indicates that combining health education with hypertension exercise can serve as an effective promotive and preventive approach to hypertension control among the elderly at the community level.